The Mechanism For Transferring Building Use Rights Is The Decision Of The Minister Of Agrarian Affairs And Spatial Planning/Head Of The National Land Agency Number 1339/Sk-Hk.02/X/2022 Of 2022 Concerning The Granting Of Land Rights In General (Case Study At Notary And Ppat Mulyani's Office) - Eka Prasetyo, Allif; Asyhadi, Farhan; Guntara, D (Universitas Muhammadiyah Sumatera Utara, 2024)
This article discusses the mechanism for transferring Building Use Rights (HGB) to Ownership Rights based on the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1339/SK-HK.02/X/2022. The case study was conducted at the Mulyani S.H., M.Kn., Karawang Notary and PPAT Office. This transition process is important to provide legal certainty and increase the economic value of land. The research uses an empirical juridical approach by collecting primary data through observation and interviews as well as reviewing written and unwritten legal materials. The research results show that the transition of HGB to Ownership Rights involves document verification, tax payment, and monitoring of processing status at the Land Office. Obstacles faced include completeness of documents, limited administrative staff, and lack of public understanding of the importance of transferring rights. The solutions implemented include verifying the validity of documents, ensuring tax payments, and regular monitoring. This transformation of land status provides stronger legal force and can be inherited indefinitely, thus increasing the selling value of the land